2013
DOI: 10.2494/photopolymer.26.415
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency Technology of White OLEDs

Abstract: High-performance all-phosphorescent white devices on a light outcoupling substrate which comprised high-index materials were investigated. The two-unit device composed of the red/blue and red/green phosphorescent units on the light outcoupling substrate achieved high light coupling efficiency of 49%. An electrically and optically optimized two-unit of all phosphorescent white OLED realized low driving voltage of 5.5 V, high luminous efficacy of 114 lm/W and half decay lifetime of over 120,000 h at 1,000 cd/m 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The research group of Panasonic has also reported several methods to enhance the LEE. For example, highly efficient OLED devices by employing the highly refractive substrate like PEN (polyethylene naphthalate) film and the micro lens array structure which is fabricated by highly refractive polymer materials were studied [15][16][17][18][19][20]. In addition, highly reflective electrode to maximize synergy effect of microstructure was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The research group of Panasonic has also reported several methods to enhance the LEE. For example, highly efficient OLED devices by employing the highly refractive substrate like PEN (polyethylene naphthalate) film and the micro lens array structure which is fabricated by highly refractive polymer materials were studied [15][16][17][18][19][20]. In addition, highly reflective electrode to maximize synergy effect of microstructure was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…5) The other is an in-plane decoration of the layers. Numerical examples have been proposed including, a diffraction lattice, 6) plasmonic crystals, 7) periodic corrugation, 8) photonic crystals, 9,10) micro-lens or randomphased arrays, [11][12][13][14][15][16][17] and scattering. [18][19][20] The theoretical design methods include geometrical ray tracing, 12) a Monte Carlo method, 15) and rigorous coupling wave analysis (RCWA).…”
mentioning
confidence: 99%